2018
DOI: 10.1007/s11047-018-9715-9
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up genetic circuit design for cellular computing: advances and prospects

Abstract: Synthetic biology aims to engineer and redesign biological systems for useful real-world applications in biomanufacturing, biosensing and biotherapy following a typical design-build-test cycle. Inspired from computer science and electronics, synthetic gene circuits have been designed to exhibit control over the flow of information in biological systems. Two types are Boolean logic inspired TRUE or FALSE digital logic and graded analog computation. Key principles for gene circuit engineering include modularity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 201 publications
(255 reference statements)
0
56
0
Order By: Relevance
“…18). Thus, the seven split inteins tested were validated to be able to implement Boolean logic computation in vivo 37 .…”
Section: Orthogonal Inteins In Vivomentioning
confidence: 99%
“…18). Thus, the seven split inteins tested were validated to be able to implement Boolean logic computation in vivo 37 .…”
Section: Orthogonal Inteins In Vivomentioning
confidence: 99%
“…We showed that, in this controller architecture, there is a trade-off between robustness to environmental disturbances and robustness to perturbations in available resources to the genetic circuit. Placing different genetic circuit components in multiple cells has been proposed as a possible solution to relieve some resource sharing effects for larger genetic circuits [15], [21], [32]. However, our analysis shows that when fluctuations in cellular resources are considered, it is not possible to tune the population controller to be both robust to extracellular disturbances and to intracellular disturbances.…”
Section: Discussionmentioning
confidence: 88%
“…In synthetic biology, the digital response is a property that is helpful in signal amplification and cascade control, [ 64–66 ] and is frequently achieved by the introduction of a positive feedback loop that steepens the response curve. [ 67–71 ] Construction of such loops using CRISPRa in bacteria has long been a challenge due to insufficient dynamic range and limitation of high basal expression. Since our CRISPRa overcame such issues, we were able to implement a positive feedback loop to achieve a digital response.…”
Section: Design Principles Learned From the Eukaryote‐like Crispramentioning
confidence: 99%